Mathematical modeling of drying kinetics of kino bark (Cucumis metuliferus) (Research, Society and Development, 2020)
The objective of this work was to perform the chemical and physical characterization of the kino bark (Cucumis metuliferus) as well as to evaluate through mathematical modeling the drying kinetics at different temperatures. The barks were characterized in natura for water content, total and soluble solids, water activity, ashes, pH, total titratable acidity, Ratio and ascorbic acid. The drying kinetics at 60, 70, 80 and 90 °C were determined by adjusting the data to twelve mathematical models using the coefficient of determination (R2) and the mean square deviation (DQM) as adjustment criteria. The kino barks showed high water content and water activity, with relatively low acidity and ash parameters and satisfactory contents of ascorbic acid, total and soluble solids. Ten of the models tested presented satisfactory adjustments to the drying kinetics data, highlighting the Page and Diffusion Approximation models, with R²> 0.999 and DQM